Pengukuran derajat keparahan maloklusi dengan menggunakan Index of Compexity Outcome and Need (ICON) di Sekolah Dasar YBPK dan Sekolah Dasar Negeri Pacar Kembang V Surabaya - Gerry Kasparianto (Faculty of Dental Medicine, Universitas Airlangga, 2011)
Background: Awareness of the age related situation as to the malocclusion prevalence in population and orthodontic treatment need is very important and useful for planning an orthodontic care, especially taking into account the interdisciplinary aspect of the problem Purpose: The purpose of this study was to investigate the degree of severity of malocclusion and the need of orthodontic treatment at SDN Pacar Kembang V and SD YBPK by using Index of Complexity, Outcome and Need (ICON) Methods: The orthodontic treatment complexity and need of 50 adolescents drawn from 2 elementary schools in Surabaya, aged 12 years were examined using the ICON. The ICON is an index of treatment need, severity of malocclusion, and treatment outcome and as such offers significant advantages over other indices of treatment need. The aesthetic component of the IOTN, crossbite, upper arch crowding or spacing, overbite or open bite, and buccal segment posterior relations are used to determine treatment need, treatment outcome, complexity, and degree of improvement used scor there was evaluated with Wilcoxon sign rank test. Result: Sampel from SDN pacar Kembang V ( n =30) and SD YBPK ( n= 20 ) has been evaluated by using The Index of Complexity, Outcome and Need (ICON) for the assessment of the results. There wasn’t significant difference between two elementary schools.Conclusion: The overall prevalence malocclusion and treatment need at two elementary schools is easy 6%, mild 48%, moderate 40%, difficult 6%, very difficult 0%.